2011
DOI: 10.3109/10826084.2011.620053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alcoholic Liver Disease Among Korean Adults: Results From the Fourth Korea National Health and Nutrition Examination Survey, 2009

Abstract: ALD is still a burden in the Korean population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In China, alcohol abuse has been considered the second leading cause of liver disease (2). A similar trend of alcohol consumption-associated burden of disease, in particular ALD, has also been seen in Korea (3,4), as well as in Japan (5,6).…”
Section: Introductionmentioning
confidence: 82%
“…In China, alcohol abuse has been considered the second leading cause of liver disease (2). A similar trend of alcohol consumption-associated burden of disease, in particular ALD, has also been seen in Korea (3,4), as well as in Japan (5,6).…”
Section: Introductionmentioning
confidence: 82%
“…We defined significant alcohol consumption based on the threshold of ≥210 g/week (men) and ≥140 g/week (women) and discriminated between NAFLD and AFLD accordingly (15). A standard drink was defined as having 10 g of ethanol, which comprises 150 mL of wine, 200 mL of beer, 50 mL of spirit, or 50 mL of Soju, the most popular alcoholic beverage among Koreans 14. The total amount of alcohol consumed per week on average was obtained by multiplying the weekly frequency ((a) 7 for once daily (b) 5.5 for 5-6 times per week (c) 3.5 for 3-4 times per week (d) 1.5 for 1-2 times per week (e) 0.75 for 2-3 times per month (f) 0.25 for less than once a month) by the consumption amount on a single occasion, at 10 g per drink.…”
Section: Methodsmentioning
confidence: 99%
“…Excess alcohol increases CVD risk because the beneficial increase in high-density lipoprotein cholesterol (HDL-C) is offset by increased blood pressure levels 13. However, despite its high prevalence and the substantial side effects involved, there has been limited research into AFLD not only in Korea but also on the international level 14. Alcohol is a causal factor in 60 types of diseases and injuries and a component cause in 200 others 2.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been no official reports regarding the prevalence of ALD and the proportion of alcohol-related causes for liver cirrhosis in Korea, studies based on inpatient data found 25-30% cases of liver cirrhosis have an alcoholic etiology 13,14. According to recent Korean studies based on data from the 2009 KNHANES, approximately 7% of Korean adults are heavy alcohol consumers (men: >40 g/day, women: >20 g/day),15,16 and approximately 25% of these heavy alcohol consumers exhibit abnormal liver-function test results 16. Since most cases of ALD occur in patients with alcohol use disorder, a brief discussion thereof is presented in the following section.…”
Section: Epidemiologymentioning
confidence: 99%